Alternative Particle Formation Pathways in the Eastern Tropical North Pacific's Biological Carbon Pump. Issue 7 (24th July 2018) - Cavan, E. L.; Giering, S. L. C.; Wolff, G. A.; Trimmer, M.; Sanders, R.
Abstract: A fraction of organic carbon produced in the oceans by phytoplankton sinks storing 5–15 gigatonnes of carbon annually in the ocean interior. The accepted paradigm is that rapid aggregation of phytoplankton cells occurs, forming large, fresh particles which sink quickly; this concept is incorporated into ecosystem models used to predict the future climate. Here we demonstrate a slower, less efficient export pathway in the Eastern Tropical North Pacific. Lipid biomarkers suggest that the large, fast‐sinking particles found beneath the mixed layer are compositionally distinct from those found in the mixed layer and thus not directly and efficiently formed from phytoplankton cells. We postulate that they are formed from the in situ aggregation of smaller, slow‐sinking particles over time in the mixed layer itself. This export pathway is likely widespread where smaller phytoplankton species dominate. Its lack of representation in biogeochemical models suggests that they may be currently overestimating the ability of the oceans to store carbon if large, fast‐sinking, labile particles dominate simulated particle export. Plain Language Summary: The oceans are one of the largest sinks of atmospheric carbon dioxide on our planet. One method by which this occurs is through the production of organic material (phytoplankton—plant‐like cells) in the surface ocean, which capture atmospheric carbon dioxide during photosynthesis. Eventually, the phytoplankton die and sink out of the surface ocean, transporting huge amounts of carbon to the deep ocean where it is stored for centuries or even millennia. Our current understanding is that generally, most organic material sinks quickly as large, fast‐sinking (hundreds of meters per day) particles (clumps of dead phytoplankton cells). However, in our study in the Equatorial Pacific Ocean, we were able to show that a different and much slower process occurs where phytoplankton first aggregate to smaller, slower sinking detrital particles and eventually form very degraded larger particles that sink to the deep. This has consequences for estimating ocean carbon storage as smaller particles are respired much quicker than larger particles. Thus, where they are an important part of this carbon sink, such as in the Equatorial Pacific, the proportion phytoplankton‐captured atmospheric carbon dioxide being stored in the deep ocean is likely reduced. Key Points: In the Eastern Tropical North Pacific large, fast‐sinking, organic particles were refractory and not formed directly from phytoplankton cells Particle aggregation occurred over time through the initial formation of smaller, suspended, and slow‐sinking particles This alternative particle formation has not been previously described and likely persists where small phytoplankton species dominate